Wobble tRNA modification and hydrophilic amino acid patterns dictate protein fate - Francesca Rapino (Nature Portfolio, 2021)
Wobble uridine (U34) tRNA modifications are important for the decoding of AA-ending codons. Here the authors show that while the U34-codon content of mRNAs are predictive of changes in ribosome translation elongation, the resulting outcome in protein expression also relies on specific hydrophilic motifs-dependent protein aggregation and clearance.